(untitled) (Huellas, 2022)
Among the debates around mining policy in Argentina, references to the ownership of resources stand out. The constitutional article that recognizes the original domain of the provinces over natural resources is usually pointed to as a lock that would prevent the articulation of a national mining policy with greater degrees of sovereignty. Partial results of an analysis of the mining legal regime in Argentina are presented here. It is intended to think about "access to resources", an empirical dimension that involves a diversity of complex social relations that include —but exceed— the property regime. Based on an exploration of current regulations, this article aims to answer what the mechanisms for access to mining resources in Argentina are and to what extent national or sub-national state bodies can regulate them. In conclusion, it is stated that the ownership of resources is not a necessarily relevant dimension to characterize the mining policy of a country. On the contrary, it is intended to show that, in Argentina, the mining policy is guaranteed by the national State, even though the resources are provincial.